PERKEMBANGAN UNIVERSITAS MALIKUSSALEH LHOKSEUMAWE, 1969-2017 - Nadila Tasya; Mawardi .; Husaini . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACT The study, entitled "The Development of Malikussaleh University Lhokseumawe, 1969-2017", raises the question of how the University of Malikussaleh was born, the development of Malikussaleh University, and how the impact of Malikussaleh University on the surrounding community. This study aims to determine the development of Malikussaleh University from the process of stage of triggering, preparation stage until supervision stage. The method used is historical method with qualitative approach, while data collection technique using libraly research (study of literature) and field research that includes observation, documentation and interview. Based on the research that has been done, obtained the following results: The birth of Malikussaleh University is the idea of T. Abdul Wahab Dahlawy and also the figures and North Aceh Regency raise the quality of education by establishing a college. In the development of the University of Malikussaleh viewed in terms of status can be said to be slow, with time more or less 20 years, University of Malikussaleh is still a private status then changed to State University in 2001. But in terms of student development, University of Malikussaleh experienced a fairly rapid development. For the field of facilities and infrastructure of Malikussaleh University also increased by adding facilities to improve the quality of teaching and learning process. The presence of Malikussaleh University is able to contribute in supporting the development of North Aceh Regency and Lhokseumawe City. For the community, the presence of Malikussaleh University also fosters their economy by marking the birth of micro-enterprises.Keywords: Development, University.